Arterial spin labeling perfusion cardiovascular magnetic resonance of the calf in peripheral arterial disease: cuff occlusion hyperemia vs exercise - Lopez, David (J Cardiovasc Magn Reson, 2015)
BACKGROUND: Assessment of calf muscle perfusion requires a physiological challenge. Exercise and cuff-occlusion hyperemia are commonly used methods, but it has been unclear if one is superior to the other. We hypothesized that post-occlusion calf muscle perfusion (Cuff) with pulsed arterial spin labeling (PASL) cardiovascular magnetic resonance (CMR) at 3 Tesla (T) would yield greater perfusion and improved reproducibility compared to exercise hyperemia in studies of peripheral arterial disease (PAD). METHODS: Exercise and Cuff cohorts were independently recruited. PAD patients had an ankle brachial index (ABI) between 0.4-0.9. Controls (NL) had no risk factors and ABI 0.9-1.4. Subjects exercised until exhaustion (15 NL-Ex, 15 PAD-Ex) or had a thigh cuff inflated for 5 minutes (12 NL-Cuff, 11 PAD-Cuff). Peak exercise and average cuff (Cuff(mean)) perfusion were compared. Six participants underwent both cuff and exercise testing. Reproducibility was tested in 8 Cuff subjects (5 NL, 3 PAD). RESULTS: Controls had greater perfusion than PAD independent of stressor (NL-Ex 74 ± 21 vs. PAD-Ex 43 ± 10, p = 0.01; NL-Cuff(mean) 109 ± 39 vs. PAD-Cuff(mean) 34 ± 17 ml/min-100 g, p < 0.001). However, there was no difference between exercise and Cuff(mean) perfusion within groups (p > 0.6). Results were similar when the same subjects had the 2 stressors performed. Cuff(mean) had superior reproducibility (Cuff(mean) ICC 0.98 vs. Exercise ICC 0.87) and area under the receiver operating characteristic curve (Cuff(mean) 0.992 vs. Exercise 0.905). CONCLUSIONS: Cuff hyperemia differentiates PAD patients from controls, as does exercise stress. Cuff(mean) and exercise calf perfusion values are similar. Cuff occlusion hyperemia has superior reproducibility and thus may be the preferred stressor.